2023
DOI: 10.3390/ijms241411566
|View full text |Cite
|
Sign up to set email alerts
|

Serpin Family A Member 1 Is Prognostic and Involved in Immunological Regulation in Human Cancers

Abstract: Serpin family A member 1 (SERPINA1) encodes a protease inhibitor participating in many human diseases, but its value in immunoregulation and prognosis of human cancers remains unclear. In this study, through comprehensive analysis of data from The Cancer Genome Atlas (TCGA) datasets, we found that SERPINA1 was dysregulated in many cancers compared with normal tissues. SERPINA1 expression was significantly associated with prognosis, immune subtype, molecular subtype, immune checkpoint (ICP) genes, tumor mutatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Its prognostic value was observed across multiple cancer types, yet its role varies among different malignancies. A recent study by Kuai X. et al found that increased SERPINA1 expression is linked to improved overall survival rates in BRCA, COAD, SARC, and SKCM, but worse survival rates in GBMLGG, HNSC, LGG, LIHC, and LUSC ( Kuai et al, 2023 ). This research further confirmed its important function as a standalone predictor in forecasting the outcome of breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Its prognostic value was observed across multiple cancer types, yet its role varies among different malignancies. A recent study by Kuai X. et al found that increased SERPINA1 expression is linked to improved overall survival rates in BRCA, COAD, SARC, and SKCM, but worse survival rates in GBMLGG, HNSC, LGG, LIHC, and LUSC ( Kuai et al, 2023 ). This research further confirmed its important function as a standalone predictor in forecasting the outcome of breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…SerpinA knockout alters the expression of genes related to inflammation and lipid metabolism in the liver [51,54]. SerpinA is also associated with the prognosis of patients with hepatic cancer [54,55]. Based on the above evidence, serpinA is thought to be involved in different hepatosteatosis conditions in db-HF and db-HC mice.…”
Section: Discussionmentioning
confidence: 99%
“…It belongs to the serine protease inhibitor family, also known as serpins. Alpha 1 antitrypsin is produced in the liver and plays a critical role in inhibiting neutrophil elastase, which helps fight infection and prevent lung damage [ 124 ]. alpha1-AT’s inhibition of proteases may reduce the breakdown of the extracellular matrix, thereby reducing the rate of AAA growth.…”
Section: Prognostic Protein Categorization and Functionsmentioning
confidence: 99%